IMPLEMENTASI BACKEND SISTEM INFORMASI HUMAN CAPITAL DI PT PERTAMINA GEOTHERMAL ENERGY AREA KAMOJANG - Adhatiyah, Risna; Nugraha, Yopi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information technology encourages organizations to adopt digitalization across various business processes, enabling administrative activities to be carried out more effectively and efficiently. The Human Capital Division of PT Pertamina Geothermal Energy Area Kamojang still faces several challenges in administrative management because some processes have not been optimally integrated, including employee data management, partner administration, correspondence, and internship disposition management. This study develops a web-based Human Capital Information System using the CodeIgniter 4 framework as the system development technology. The system development method applied is Agile Scrum with an iterative approach. The application is built using PHP, MySQL, and Bootstrap 5. The implementation results indicate that the system is capable of integrating employee management, partner management, certification records, correspondence, dispositions, and monthly reporting within a centralized platform. The system also improves data accessibility while reducing data duplication and errors. Therefore, the developed system can support the optimization of administrative processes and digital transformation within the Human Capital Division of PT Pertamina Geothermal Energy Area Kamojang.